The Iindaba Ziyafika project: a new community of practice?,The Indaba Ziyafika project - Nyathi, Sihle (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2011)
This study sought to investigate the practices of citizen journalists in the Iindaba Ziyafika project. The objectives of the research were to explore the evolving practices of citizen journalism in Grahamstown and to extrapolate how citizen journalists are securing a discursive space in relationship to conventional journalism. The study investigated whether the citizen journalists based at Grocotts Mail and Radio Grahamstown are developing practices and patterns that can be distinguished from the practices of conventional journalism. It also evaluated whether the content that is produced by citizen journalists differs from the content that is produced by professional journalists, so that it can be understood as "alternative" and as promoting engaged citizenship. A sub goal was also to explore whether citizen journalism does enable the practice of citizenship through expanding the public sphere. The findings of the research are that in the Iindaba Ziyafika project, citizen journalists see news as a process and not as a series of news events. This is clear departure from event-based news conceptualisation associated with mainstream journalism. They view news as unfolding social processes, allowing citizen journalists to question the factors which would have precipitated the event and investigate the causal factors of particular phenomena. The research also reveals that citizen journalists in the project are engaging in pro-am journalism. Part of the practice of citizen journalists involves a very significant amount of collaboration between professional journalists and citizen journalists. The collaboration is in the production of content and in the presentation of radio broadcasts. Part of the findings of the study are that journalists in the Iindaba Ziyafika project work in different mediums and this calls for them to acquire the competencies of the different mediums. The same citizen journalists produce content for print, radio and for online media. The diction used in the stories published by citizen journalists is couched in struggle and revolutionary language which seems to pit the community against the authorities. The citizen journalists also make use of every daily language in their radio broadcasts and borrow from their cultural expression. This they do through populist methods. The citizen journalists have also integrated communication brokering as part and parcel of their practice. This is because the citizen journalists have also made it their mandate to enable the flow of information between the residents and the local authority. In terms of sourcing there is a deliberate stance to include those who are not ordinarily given a voice in the mainstream media. Women and the poor appear frequently in stories as sources and this is a different scenario from that prevalent in mainstream journalism which frequently covers the rich and the powerful. The citizen journalists in the Iindaba Ziyafika project have also borrowed practices from professional journalism and this has been integrated into their daily practice. This includes following strategic rituals of journalism objectivity and balance.
Keywords: Citizen journalism -- South Africa -- Grahamstown; Journalism -- South Africa -- Grahamstown; Iindaba Ziyafika project; Grocott's Mail (Grahamstown, South Africa); Radio journalism -- South Africa -- Grahamstown; Online journalism -- South Africa -- Grahamstown; Mass media -- Social aspects -- South Africa -- Grahamstown; Mass media -- Political aspects -- South Africa -- Grahamstown; Journalism -- Objectivity -- South Africa -- Grahamstown